Blended learning in physical education: application and motivation - Hrušová, Dagmar; Chaloupský, David; Chaloupská, Pavlína; Hruša, Petr (Frontiers in Psychology, 2024)
Background: The aim of the research was to evaluate outdoor aerobic sport activities (OASA) in physical education (PE) of university students, using wearables and their potential to personalize the learning process and enhance motivation. Methods: 368 university students participated. The OASA structure and the key points of application in PE were described. Descriptive statistics of the training units (n = 3680) were processed. The students recorded their training data in Strava app (10 sessions per semester) and the data was shared in the online sport community created on Strava platform. Motivation was evaluated in a questionnaire. The focus was both on intrinsic motivation and extrinsic “ICT” motivation, based on Strava app features and tools. Results: The most preferred outdoor aerobic sport activities were: running (58%), cycling (13%) and walking (16%). The results provided insight into motivation and performance analysis. Students’ motivation to participate in OASA was mainly in health concerns, such as stay in shape (94%) or stay healthy (90%) and psychological concerns, such as have fun (88%), improve state of mind (88%) or relieve stress (83%). In achievement concerns the motivation was in a personal challenge (72%), while competing with others was ranked lowest (32%). Strava app was a motivating tool for students to record, monitor and analyze their individual activities and feel “connectedness” to the online sport community. 70% students were motivated by a non-competitive character of PE, that gave them a personalized opportunity to train without being compared to the others. Discussion: The OASA management with use of blended learning methods and Strava app is a motivational approach to create, support and maintain students’ healthy habit of physical activity through PE lessons. The need of students to be motivated to exercise can be confirmed in analysis of the statistical descriptive parameters of running, cycling and walking. There was a tendency of students to complete only the minimum required distance/time (not more). On the other hand, students enjoyed the training and 99% students confirmed that they would enroll again. That fact underlined the importance of motivating students by an effective learning strategy, giving support and guidance.